Broad ligament hernia as a rare cause of acute small bowel obstruction: A wolf in sheep’s clothing – A case report with review of the literature - Rafique Umer Harvitkar,; Bhavesh Shelke,; Abhijit Joshi, (Indian Journal of Case Reports, 2020)
Broad ligament hernia (BLH) is a rare clinical entity. It is a potentially life-threatening, yet often neglected and sometimes misdiagnosed surgical condition. We, herein report a case of acute small bowel obstruction in a 42-year-old female caused by internal herniation of the small bowel through a defect in the left broad ligament, which was successfully managed laparoscopically. We also reviewed the literature on BLH and present our recommendation on the diagnosis and management of BLH.